Improving Writing Ability on Narrative Text Material Using Gamification Method In Class 3 Students Of SDN 2 Seren - Amanda Putri, Chisa; Fatona, Anisatul; Ratnaningsih, Arum (Genderang Asa: Journal of Primary Education, 2025)
Writing ability is an important aspect of learning Indonesian that must be mastered by students in elementary school. Writing is not just about expressing ideas in written form, but also involves the ability to organize, assemble and present thoughts systematically. One type of writing skill that is important to develop in elementary school students is narrative writing. The aim of this research is to improve narrative text writing skills using the gamification method for grade 3 students at SDN 2 Seren. This research is classroom action research (PTK) which was carried out in 2 cycles. Data collection techniques in this research include observation, tests and interviews. The research results show that application of the method gamification showed a significant increase in hresult student learning in cycle I meninlevel to 84% in cycle II. The average in cycle I was 66.15, increasing to 80.21 in cycle II. This increase proves bawah onThe use of gamification methods can improve the ability to write narrative texts of grade 3 students at SDN 2 Seren.